Evaluación de la eficiencia energética del CO2 producido en el Campo Cerro gordo de la Cuenca del Catatumbo mediante un modelo económico (2020)
The Carbonera Block, located in the middle area of ​​the Norte de Santander department (Colombia), is a concession granted since 2005 to the Well Loging company, now identified as Wattle Petroleum Company, for the exploitation and production of hydrocarbons. Most of its production stands out for being light hydrocarbons with a significant presence of CO2, which is considered a pollutant; In addition to these components, production also has a smaller scale proportion of water and condensate. "Meeting the needs of present generations without compromising the possibilities of future generations to meet their own needs" has been one of the most important premises on which the scientific community has relied to find viable options that allow preserving the environment and keep the energetic rhythm of the needs of the current world. The present work of degree exposes the economic viability of an innovative technology that implements the electrochemical transformation of carbon dioxide to generate a compound with a high energetic power which is known as methanol. This technology was developed by the engineer Jacob Karni, a professor at the Weizsmann Institute in Israel, together with his team and after eight years of research he managed to lay the foundations for this project, which has been in the commercial phase since 2017.